Belanja Pemerintah Daerah: Bagaimana Alokasi Belanja Publik yang Pro Poor Expenditure di Kabupaten Kulon Progo Yogyakarta? - Ariyad, Fikri; Choirunnisa (Ministry of Home Affairs, 2023)
This article aims to show the public expenditure of the Kulon Progo Regional Government responds to welfare issues with a pro-poor budget approach. Currently, Kulon Progo Regency is still the area with the highest poverty rate among regencies/cities in D.I.Yogyakarta. This condition becomes ironic because this area is under the Regional Government, which has the status of receiving special autonomy. This arrangement impacts the disbursement of special funds to Kulon Progo so that its fiscal capacity becomes large. This type of research uses a qualitative approach with the library research method. While the stages of this research consisted of problem identification, literature search, research aims and objectives, data collection, data analysis and interpretation, and research reporting. The study results show that Kulon Progo's public expenditure has not been able to bring this region out of the issue of inequality. The issue of poverty, the low human development index, the high open unemployment rate, and even the low allocation of public expenditure on infrastructure impacts the predicate and image of Kulon Progo, which has not been separated from this issue. In addition, in the aspect of public expenditure, especially based on budget allocations that are pro-poor, in fact, they have not fully accommodated their interests. This can be seen from the data analysis on the issue of inequality in the Kulon Progo Regency, which has not been properly resolved. This reality in the context of Kulon Progo is interesting to study because, with a large enough fiscal power capacity, it has not been reflected in public expenditure oriented towards the people’s welfare.